Early Results of Trans-Oral Endoscopic Plication and Revision of the Gastric Pouch and Stoma following Roux-en-Y Gastric Bypass Surgery - Leitman, I. Michael (Society of Laparoendoscopic Surgeons, 2010)
OBJECTIVE: A new technique for endoscopic plication and revision of the gastric pouch (EPRGP) for patients who underwent gastric bypass (RGB) surgery was evaluated in patients with severe GERD, dumping syndrome, failure of weight loss, or all of these. PATIENTS AND METHODS: Patients underwent EPRGP over a 12-month period. The StomaphyX device (Endogastric Solutions, Redmond, WA) was utilized over a standard flexible gastroscope. Patients were kept on a liquid diet for 1 week. RESULTS: The study included 64 patients with a mean age of 48 years who underwent 67 procedures. EPRGP was performed an average of 5 years after RGB. The mean preoperative BMI was 39.5 kg/m(2). The primary indications for the procedure were inadequate weight loss, dumping syndrome (42), and GERD (15). The mean follow-up period was 5.8 months (range, 3 to 12). The average operative time was 50 minutes, with a significant reduction with increased operator experience. There were only 2 (3%) intraoperative complications during the early period (equipment failure), which did not result in any morbidity. All symptoms from dumping syndrome or reflux improved, with no further operative-related complications. The mean weight loss was 7.3kg. CONCLUSIONS: This study demonstrates the technical feasibility, safety, and efficacy of EPRGP.